A validated thermo mechanical FEM model of bead-on-plate welding. (1st January 2014) - Darmadi, Djarot B.; Kiet-Tieu, Anh; Norrish, John
This paper is presenting accurate FEM model of bead-on-plate welds of 316L stainless steels through thermo-mechanical analysis. The model was composed using ANSYS Parametric Design Language (APDL) program. In thermal analysis, mixed mode of volumetric thermal load was used to represent moving heat source. Growing weld bead was accommodated in both the thermal and mechanical models using birth and death technique. Melting phenomenon was modelled by low stiffness and zero plastic strain of melting elements. Results from thermal analysis and subsequent mechanical analysis have been validated. Good agreements of predicted temperature histories, temperature field and residual stress with experimental results confirmed the accuracy of the proposed FEM model.